1997
DOI: 10.1007/s11746-997-0091-3
|View full text |Cite
|
Sign up to set email alerts
|

Mixtures of palm kernel oil with cocoa butter and milk fat in compound coatings

Abstract: Thermal behavior of binary mixtures of palm kernel oil (PKO), cocoa butter (CB), and anhydrous milk fat was used to study mixed-lipid crystallization. This study was related to the physical properties of compound coatings made with these fats. Phase behavior was studied by evaluating changes in melting behavior with composition and time, by creating isosolid diagrams, and by monitoring polymorphic behavior. For binary mixtures, multiple melting peaks and eutectic formation were observed for 30-50% addition lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
2
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 10 publications
5
36
2
1
Order By: Relevance
“…HPKO contained high amount of lauric and palmitic acids, i.e., 48.2% and 18.0% respectively whereas the butter had high amount of palmitic, 30.0% and oleic acids 40.0% (Table 1). The composition of lauric and palmitic acid in the HPKO were reported as 49.9% and 9.9% respectively (Williams et al,1997). The PV, IV and FFA of HPKO were found 0.46 meq/kg, 6.8 and 0.002% respectively while butter showed 5.65 meq/kg, 0.63 and 0.06%.…”
Section: Physico-chemical Characterisation Of Blended Samplesmentioning
confidence: 94%
See 2 more Smart Citations
“…HPKO contained high amount of lauric and palmitic acids, i.e., 48.2% and 18.0% respectively whereas the butter had high amount of palmitic, 30.0% and oleic acids 40.0% (Table 1). The composition of lauric and palmitic acid in the HPKO were reported as 49.9% and 9.9% respectively (Williams et al,1997). The PV, IV and FFA of HPKO were found 0.46 meq/kg, 6.8 and 0.002% respectively while butter showed 5.65 meq/kg, 0.63 and 0.06%.…”
Section: Physico-chemical Characterisation Of Blended Samplesmentioning
confidence: 94%
“…HPKO reflected 95.2% saturates 4% MUFA and less than 1% PUFA. Williams et al (1997) reported that HPKO contained 97% saturates, 2% MUFA and less than one percent PUFA. Butter had 59.4% saturates 40% MUFA and 0.6% PUFA.…”
Section: Physico-chemical Characterisation Of Blended Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…These fats have physical properties resembling those of CB. An increasing number of reports focuses on the preparation and processing properties of CBS and the corresponding chocolate products [3][4][5][6][7][8]. An important crude oil feedstock of such confectionery fats is palm kernel oil (PKO), especially being hydrogenated (HPKO) or fractionated (FPKO), which can be used in place of a major part of CB that is present in normal chocolate.…”
Section: Introductionmentioning
confidence: 99%
“…Mixing with CB results in a eutectic state which will lead to a softening and phase separation of chocolate products and eventually the formation of bloom. Several theories to explain these blooming phenomena have been proposed [3,7,[9][10][11], but so far none seems to be unanimously approved. Williams et al [3] found that polymorphic transitions cannot explain formation of bloom until the CB content was greater than 40%.…”
Section: Introductionmentioning
confidence: 99%